LncRNA LINC00963 promotes osteogenic differentiation of hBMSCs and alleviates osteoporosis progression by targeting miRNA-760/ETS1 axis. (18th August 2021) - Ren, Lirong; Guo, Limin; Kou, Nannan; Lv, Jia; Wang, Zhihua; Yang, Kaishun
Abstract: Although long non-coding RNA LINC00963 has been reported to play a crucial regulatory role in osteoporosis (OP), its specific mechanism has not been well studied. Cell viability of human bone marrow mesenchymal stem cells (hBMSCs) transfected with short hairpin RNA targeting LINC00963 (sh-LINC00963) and negative control (sh-NC) was analysed by cell counting kit-8 (CCK-8) assay. Alkaline phosphatase (ALP) activity in hBMSCs transfected with sh-LINC00963 and sh-NC after induction by osteogenic medium (OM) on day 7 was detected. The protein expression levels of osteocalcin (OCN) and osteopontin (OPN) in hBMSCs transfected with sh-LINC00963 and sh-NC during OM induction on day 3 were detected by western blot. The relationship among LINC00963, miR-760, and E26 transformation specific-1 (ETS1) was determined by bioinformatics analysis, luciferase reporter assay, and RNA-binding protein immunoprecipitation (RIP) assay. A rat model with OP was established to confirm the role of LINC00963 in vivo . The expression level of LINC00963 was much lower in hBMSCs isolated from the discarded femoral head tissues of OP patients compared with that in health patients. Meanwhile, the expression level of LINC00963 was significantly increased and the expression level of miR-760 was decreased in hBMSCs during osteogenic induction. LINC00963 could bind to the 3′-untranslated region (3′-UTR) of miR-760 and negatively regulate the expression of miR-760, then promote the osteogenic differentiation in hBMSCs. ETS1 was identified as a target of miR-760. Moreover, overexpression of LINC00963 obviously reduced bone mineral density (BMD) of the left femur in OP rats and alleviated OP progression in vivo. Our results demonstrated that LINC00963 positively regulated the expression of ETS1 by directly targeting miR-760, and then promoted osteogenic differentiation of hBMSCs in vitro, and also attenuated OP progression in vivo, suggesting that LINC00963 might be a potential therapeutic target for OP.